Role hemoxygenázy v patogenezi jaterního poškození u chronické HCV infekce - Urbánek, Petr (Iga MZ ČR, 2011)
In the presented project, the role of hemooxygenase 1 and 2 in the procesess associated with fibroproduction in the chronic HCV infection will be studied. Hemooxygenase expression will be evaluated by the techniques of molecular genetics and immunohistochemistry, both in the liver tissue and in peripheral blood mononuclear cells. These parameters will be correlated with basic virological and clinical characteristics of the chronic HCV infection. Our expected results may help understanding the mechanismsof fibroproduction in chronic HVC infection and, therefore, contribute to explain individual differences in the development of chronic HCV infection.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: hepatologie; Oxidative Stress; biochemie; Hepacivirus; Liver Cirrhosis; infekční lékařství; hemoxygenasa-1; jaterní cirhóza; Heme Oxygenase-1; Hepatitis C, Chronic; chronická hepatitida C; oxidační stres